Human brown adipose tissue [15O]O2 PET imaging in the presence and absence of cold stimulus - u Din, Mueez; Raiko, Juho; Saari, Teemu; Kudomi, Nobu; Tolvanen, Tuula; Oikonen, Vesa; Teuho, Jarmo; Sipilä, Hannu T; Savisto, Nina; Parkkola, Riitta; Nuutila, Pirjo; Virtanen, Kirsi A. (European journal of nuclear medicine and molecular imaging, 2016)
Purpose Brown adipose tissue (BAT) is considered a potential target for combatting obesity, as it produces heat instead of ATP in cellular respiration due to uncoupling protein-1 (UCP-1) in mitochondria. However, BAT-specific thermogenic capacity, in comparison to whole-body thermogenesis during cold stimulus, is still controversial. In our present study, we aimed to determine human BAT oxygen consumption with [ 15 O]O 2 positron emission tomography (PET) imaging. Further, we explored whether BAT-specific energy expenditure (EE) is associated with BAT blood flow, non-esterified fatty acid (NEFA) uptake, and whole-body EE. Methods Seven healthy study subjects were studied at two different scanning sessions, 1) at room temperature (RT) and 2) with acute cold exposure. Radiotracers [ 15 O]O 2 , [ 15 O]H 2 O, and [ 18 F]FTHA were given for the measurements of BAT oxygen consumption, blood flow, and NEFA uptake, respectively, with PET-CT. Indirect calorimetry was performed to assess differences in whole-body EE between RT and cold. Results BAT-specific EE and oxygen consumption was higher during cold stimulus (approx. 50 %); similarly, whole-body EE was higher during cold stimulus (range 2–47 %). However, there was no association in BAT-specific EE and whole-body EE. BAT-specific EE was found to be a minor contributor in cold induced whole-body thermogenesis (almost 1 % of total whole-body elevation in EE). Certain deep muscles in the cervico-thoracic region made a major contribution to this cold-induced thermogenesis (CIT) without any visual signs or individual perception of shivering. Moreover, BAT-specific EE associated with BAT blood flow and NEFA uptake both at RT and during cold stimulus. Conclusion Our study suggests that BAT is a minor and deep muscles are a major contributor to CIT. In BAT, both in RT and during cold, cellular respiration is linked with circulatory NEFA uptake.